The Optimum Priorities In Improving The Infrastructure Of Al-Anbar Governorate Road Network Using R.S. Data, GIS And Graph Theory - Sabbar M. al-Shuqairy, Majid (Anbar Journal of Engineering Sciences, 2018)
The status of the infrastructure of the transport system and then mobility in the governorate of Anbar is deplorable. Therefore, it requires two types of solutions in two phases. This study concerned with the first phase, which is represented by solving the problem of the inadequacy infrastructure in terms of availability between the cities, and work to develop it toward being maximally connected. So, generally speaking this study aimed to facilitate mobility through this network, by improving the accessibility in term of connectivity. The analysis process in this study, have twin objectives: first, to determine how much new linkages we need for our network to be maximally connected as a first stage? Second, Building a legislative framework lends the weight for decision makers in transport agency to take tough decision built up on ranking the new proposed linkages according to their relative values in providing access to the network, and the increment in comparable nodal accessibility due to the new additions. So, there is need for more sensible decisions based on more accurate analysis for deciding the optimum priorities for the new linkages to take place in the stage of development implementation via legislative framework. Therefore, the analysis will deal with topological characteristics for a number of aspects by expressing the simple graph of the network in a matrix format. These aspects are simulated and measured through the matrices powering process and the principles of graph theory. However, in addition to reducing the time the vehicles stays on the road, the study results will assist to divert a large proportion of the traffic volumes concurrently with the implementation process, and this in turn will pave the way to precede the solution of the second phase inside the cities. Not to mention, the legislative framework will bases for the financial framework of the transport agency. Keywords: infrastructure inadequacy& development, accessibility and connectivity, graph theory, matrix representation &powering, new linkage, nodal accessibility , relative value ,optimum priorities (ranking) and Decision making(legislation).